STRATEGI PENGELOLA KURSUS MENJAHIT UNTUK MENGEMBANGKAN PERILAKU WIRAUSAHA DI LKP SARI MEDAN - Cindy Nadya Silalahi; Anifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze and describe the strategies employed by the management of a sewing course institution in developing entrepreneurial behavior among trainees at Lembaga Kursus dan Pelatihan (LKP) Sari Medan. The study used a qualitative descriptive approach. Research participants were selected through purposive sampling and consisted of one institution manager, one sewing instructor, and two female trainees. Data were collected through observations, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model, including data collection, data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that the management implemented two main strategies, namely providing beneficial learning activities and sustainable empowerment activities. These strategies were realized through gradual sewing skills training, intensive mentoring, professional work attitude development, customer service ethics, and continuous motivation to encourage participants to establish independent businesses. The program also fostered entrepreneurial behavior, including discipline, responsibility, creativity, and self-confidence. Supporting factors included adequate training facilities, competent instructors, a conducive learning environment, and participants' motivation, while obstacles consisted of differences in participants' abilities, limited learning time, low initial motivation, and technical difficulties during the early stages of training. Overall, the management strategies were effective in developing participants' entrepreneurial behavior, although strengthening entrepreneurship education and post-training mentoring remains necessary to support sustainable business development.